2011
DOI: 10.5152/jtgga.2011.03
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cell type on surgico-pathologic risk factors in endometrial cancer

Abstract: Aggressive cell types significantly increase the adnexial and lymph node metastasis in endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Lymphatic spread is an important prognostic factor representing the most common extrauterine area of disease spread in endometrial cancer. Nodal metastasis is detected in 5% of women who are supposed to have low-risk endometrial cancer and 22% of women who are supposed to have moderate-risk endometrial cancer (10) 16), tumor size (17), and tumor type (18) as important factors in determining extrauterine spread. The present study identified the presence of LVI, cervical invasion, peritoneal cytology positivity and tumor type as independent prognostic factors for predicting extrauterine spread.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic spread is an important prognostic factor representing the most common extrauterine area of disease spread in endometrial cancer. Nodal metastasis is detected in 5% of women who are supposed to have low-risk endometrial cancer and 22% of women who are supposed to have moderate-risk endometrial cancer (10) 16), tumor size (17), and tumor type (18) as important factors in determining extrauterine spread. The present study identified the presence of LVI, cervical invasion, peritoneal cytology positivity and tumor type as independent prognostic factors for predicting extrauterine spread.…”
Section: Discussionmentioning
confidence: 99%
“…Hücre tiplerine göre lenf nodu metastazlarını inceleyen bir çalışmada, agresif hücre tipli endometrium kanserli olgularda pelvisin tüm bölgelerinde metastaz saptanırken, para-aortik lenf nodu metastazının hücre tipinden bağımsız olduğu bildirilmiştir (9) . Bizim çalışmamızda agresif hücre tipi komponenti olan olgularda pelvik ve para-aortik lenf nodu metastazı varlığı anlamlı düzeyde daha yüksek bulunmuştur (p=0,041).…”
Section: Discussionunclassified
“…Peritoneal sitoloji pozitifliği dört hastada, adneksiyal tutulum altı hastada ve servikal stromal invazyon 11 hastada saptandı. Omentumun değerlendirildiği 32 hastanın 30'unda (%90, 9) omental metastaz saptanmadı. Hastaların cerrahi patolojik verileri Tablo 1'de ayrıntılı olarak belirtilmiştir.…”
Section: Bulgularunclassified
“…Although ECa is the most common gynecologic cancer worldwide and numerous studies have been performed on risk factors or prognostic factors, the underlying carcinogenic mechanisms remain unknown (24,25). Unopposed and prolonged estrogen stimulation, including stimulation by nulliparity, late menopause, and obesity, has been identified as a risk factor for the development of ECa.…”
Section: Discussionmentioning
confidence: 99%